The effects of intestinal tract bacterial diversity on mortality following allogeneic hematopoietic stem cell transplantation - Taur, Ying; Jenq, Robert R.; Perales, Miguel-Angel; Littmann, Eric R.; Morjaria, Sejal; Ling, Lilan; No, Daniel; Gobourne, Asia; Viale, Agnes; Dahi, Parastoo B.; Ponce, Doris M.; Barker, Juliet N.; et al. (Blood, 2014)
Highly diverse bacterial populations inhabit the gastrointestinal tract and modulate host inflammation and promote immune tolerance. In allogeneic hematopoietic stem cell transplantation (allo-HSCT), the gastrointestinal mucosa is damaged, and colonizing bacteria are impacted, leading to an impaired intestinal microbiota with reduced diversity. We examined the impact of intestinal diversity on subsequent mortality outcomes following transplantation. Fecal specimens were collected from 80 recipients of allo-HSCT at the time of stem cell engraftment. Bacterial 16S rRNA gene sequences were characterized, and microbial diversity was estimated using the inverse Simpson index. Subjects were classified into high, intermediate, and low diversity groups and assessed for differences in outcomes. Mortality outcomes were significantly worse in patients with lower intestinal diversity; overall survival at 3 years was 36%, 60%, and 67% for low, intermediate, and high diversity groups, respectively (P = .019, log-rank test). Low diversity showed a strong effect on mortality after multivariate adjustment for other clinical predictors (transplant related mortality: adjusted hazard ratio, 5.25; P = .014). In conclusion, the diversity of the intestinal microbiota at engraftment is an independent predictor of mortality in allo-HSCT recipients. These results indicate that the intestinal microbiota may be an important factor in the success or failure in allo-HSCT. •Intestinal diversity is predictive of mortality in allo-HSCT.